2000
DOI: 10.1002/1522-2683(200011)21:17<3757::aid-elps3757>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics approach in classifying the biochemical basis of the anticancer activity of the new olomoucine-derived synthetic cyclin-dependent kinase inhibitor, bohemine

Abstract: The aim of this study was to use two-dimensional electrophoresis (2-DE) coupled with multivariate principal component analysis (PCA) to characterize the quantitative changes in the protein composition of the CEM T-lymphoblastic leukemia cell line after treatment with bohemine (BOH), a synthetic olomoucin-derived cyclin-dependent kinase inhibitor (CDKI). Cell classification, reflecting protein patterns, clearly distinguished two main groups: one group consists of 9, 12 and 24 h treated BOH cells while the secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…It has been demonstrated that red polyphenols which also contain resveratrol have a role in downregulating ubiquitin-like, containing PHD and RING finger domains 1 as an epigenetic equilibrium which regulates both DNA methylation and histone modifications. 28,29 There are evidence which clarify the correlation of resveratrol effect in the BAX and BCL2 genes in molecular levels, 30,31 although the mechanisms behind the gene regulation are yet to be comprehensively described.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that red polyphenols which also contain resveratrol have a role in downregulating ubiquitin-like, containing PHD and RING finger domains 1 as an epigenetic equilibrium which regulates both DNA methylation and histone modifications. 28,29 There are evidence which clarify the correlation of resveratrol effect in the BAX and BCL2 genes in molecular levels, 30,31 although the mechanisms behind the gene regulation are yet to be comprehensively described.…”
Section: Discussionmentioning
confidence: 99%
“…T-lymphoblastic cell line CEM was treated by bohemine and the changes of the protein composition, as visualized in two-dimensional electrophoresis, were quantitated. In bohemine treated cells, five proteins were found to be downregulated, namely α-enolase, triosephosphate isomerase, initiation factor 5A, and α-and β-subunits of Rho GDP-dissociation inhibitor 1 (Kováȓová et al, 2000). These proteins play significant roles in glycolysis, proteosynthesis, and in cytoskeleton rearrangement.…”
Section: Bohemine In Semicontinuous Culturesmentioning
confidence: 99%